Avifauna del bosque de terraza inundable por agua negra en Ninarumi – Llanchama, Río Nanay, Loreto – Perú - Yumbato Zumba, Samuel (2024)
The loss of diversity in general is worsening more and more rapidly worldwide, which is why it is necessary to study little-known habitats before they disappear, therefore, between March and August 2022 in the Ninarumi – Llanchama (Nanay River) sector. records of the ornithological fauna were made using the canoe and auditory census method, where 98 species of birds were recorded, where Brotogeris versicolurus, Aratinga weddellii, Sporophila casteneiventris and Sporophila lineola showed high densities, concluding that this forest has a high diversity of birds but low abundance.